Synthesis of α-oxycarbanilinophosphonates and their anticholinesterase activities: the most potent derivative is bound to the peripheral site of acetylcholinesterase. (June 2013) - Kaboudin, Babak; Emadi, Saeed; Faghihi, Mohammad Reza; Fallahi, Maryam; Sheikh-Hasani, Vahid
<x xml:space="preserve">Abstract</x> A novel method has been developed for the synthesis of α-oxycarbanilino phosphonates through a reaction of α-hydroxyphosphonates with isocyanate under microwave irradiation. The synthesized compounds were evaluated for their acetylcholinesterase (AChE) inhibition potency through IC50determination. Molecular modelling studies suggest that the most potent inhibitor (compound 4h, IC50 = 6.36 µM) is bound to the peripheral site of AChE, which suggests that it decreases the catalytic activity not through binding to the active site but through blocking the entrance of the active site gorge. This puts forward the potential of compound 4h and its derivatives to be used in the design of dual inhibitors: inhibition of the catalytic activity of AChE and of amyloid β aggregation.